Betulin-Based Oleogel to Improve Wound Healing in Dystrophic Epidermolysis Bullosa: A Prospective Controlled Proof-of-Concept Study - Agnes Schwieger-Briel; Dimitra Kiritsi; Christoph Schempp; Cristina Has; Hauke Schumann (Dermatology Research and Practice)
Introduction. Skin fragility and recurrent wounds are hallmarks of hereditary epidermolysis bullosa (EB). Treatment options to accelerate wound healing are urgently needed. Oleogel-S10 contains a betulin-rich triterpene extract from birch bark. In this study, we tested the wound healing properties of topical Oleogel-S10 in patients with dystrophic EB. Methods. We conducted an open, blindly evaluated, controlled, prospective phase II pilot trial in patients with dystrophic EB (EudraCT number 2010-019945-24). Healing of wounds treated with and without topical Oleogel-S10 was compared. Primary efficacy variable was faster reepithelialization as determined by 2 blinded experts. The main secondary outcome variable of the study was percentage of wound epithelialization. Results. Twelve wound pairs of 10 patients with dystrophic EB were evaluated. In 5 of 12 cases, both blinded reviewers considered epithelialization of the intervention wounds as superior. In 3 cases, only one reviewer considered Oleogel-S10 as superior and the other one as equal to control. Measurements of wound size showed a trend towards accelerated wound healing with the intervention but without reaching statistical significance. Conclusion. Our results indicate a potential for faster reepithelialization of wounds in patients with dystrophic EB when treated with Oleogel-S10 but larger studies are needed to confirm significance.